# X and Y Intercepts

date post

06-Jan-2016Category

## Documents

view

19download

2

Embed Size (px)

description

### Transcript of X and Y Intercepts

X and Y Intercepts

The y intercept is the point at which the graph of an equation crosses the y axis. y(0,3)xy = 2x + 3

The y intercept is the point at which the graph of an equation crosses the y axis. y(0,3)xNotice that the x value is zero.y = 2x + 3

The x intercept is the point at which the graph of an equation crosses the x axis. y(-3/2 ,0)xy = 2x + 3

The x intercept is the point at which the graph of an equation crosses the x axis. y(-3/2 ,0)xNotice that the y value is zero.y = 2x + 3

Example #1 Find the y and x intercepts. Then graph the line.y = 2x + 6

Example #1 Find the y and x intercepts. Then graph the line.y = 2x + 6y intercept y = 2(0) + 6 y = 6 (0,6)

Example #1 Find the y and x intercepts. Then graph the line.y = 2x + 6y intercept y = 2(0) + 6 y = 6 (0,6)x intercept 0 = 2x + 6 x = -3 (-3,0)

Example #1 Find the y and x intercepts. Then graph the line.y = 2x + 6(0,6)(-3,0)yx

Example #1 Find the y and x intercepts. Then graph the line.y = 2x + 6(0,6)(-3,0)yx

Example #2 Find the y and x intercepts. Then graph the line.y = 3x + 12

Example #2 Find the y and x intercepts. Then graph the line.y = 3x + 12y intercept y = 3(0) + 12 y = 12 (0,12)

Example #2 Find the y and x intercepts. Then graph the line.y = 3x + 12y intercept y = 3(0) + 12 y = 12 (0,12)x intercept 0 = 3x + 12 x = -4 (-4,0)

Example #2 Find the y and x intercepts. Then graph the line.y = 3x + 12(0,12)(-4,0)yx

Example #2 Find the y and x intercepts. Then graph the line.y = 3x + 12(0,12)(-4,0)yx

Practice Time

For each function, find the x and y intercepts. Then graph the line.

1) y = x + 4

1) y = x + 4y intercept y = (0) + 4 y = 4 (0,4)x intercept 0 = x + 4 x = -8 (-8,0)

1) y = x + 4(0,4)(-8,0)yx

2) y = -2 x + 8

2) y = -2 x + 8y intercept y = -2 (0) + 8 y = 8 (0,8)x intercept 0 = -2 x + 8 x = 4 (4,0)

2) y = -2 x + 8(0,8)(4,0)yx

3) y = -3x - 4

3) y = -3x - 4y intercept y = -3 (0) - 4 y = -4 (0,-4)x intercept 0 = -3 x - 4 x = -4/3 (-4/3,0)

3) y = -3x - 4(0,-4)(-4/3,0)yx

4) y = 8x - 2

4) y = 8x - 2y intercept y = 8 (0) - 2 y = -2 (0,-2)x intercept 0 = 8 x - 2 x = 1/4 (1/4,0)

4) y = 8x - 2(0,-2)(1/4,0)yx

5) 2x + 3y = 6

5) 2x + 3y = 6y intercept 2(0) + 3y = 6 y = 2 (0,2)x intercept 2x + 3(0) = 6 x = 3 (3,0)

5) 2x + 3y = 6(0,2)(3,0)yx

6) 5x + 2y = 10

6) 5x + 2y = 10y intercept 5(0) + 2y = 10 y = 5 (0,5)x intercept 5x + 2(0) = 10 x = 2 (2,0)

6) 5x + 2y = 10(0,5)(2,0)yx

7) -3x + 5y = 9

7) -3x + 5y = 9y intercept -3(0) + 5y = 9 y = 9/5 (0,9/5)x intercept -3x + 5(0) = 9 x = -3 (-3,0)

7) -3x + 5y = 9(0,9/5)(-3,0)yx

8) -2x - 3y = 10

8) -2x - 3y = 10y intercept -2(0) - 3y = 10 y = -10/3 (0,-10/3)x intercept -2x - 3(0) = 10 x = -5 (-5,0)

8) -2x - 3y = 10(0,-10/3)(-5,0)y